Preclinical disposition of MGS0274 besylate, a prodrug of a potent group II metabotropic glutamate receptor agonist MGS0008 for the treatment of schizophrenia - Kohnosuke Kinoshita; Motoki Ochi; Katsuya Iwata; Misako Fukasawa; Jun‐ichi Yamaguchi (Wiley, 2019)
Abstract MGS0274 besylate is an ester‐based lipophilic prodrug of a metabotropic glutamate (mGlu) 2 and mGlu3 receptor agonist MGS0008 and being developed for the treatment of schizophrenia. We investigated the disposition of these compounds in rats and monkeys and in vitro metabolism in humans to evaluate whether MGS0274 besylate could be useful as a prodrug in humans. After the oral administration of MGS0274 besylate to monkeys (2.89 mg/kg), MGS0008 was immediately found in plasma, reached a maximum concentration at 4 hours postdose, and decreased with a terminal half‐life of 16.7 hours; MGS0274 was barely detectable. The oral bioavailability as MGS0008 was 83.7%, which was approximately 20‐fold greater than that after oral dosing of MGS0008 (3.8%). In rats, MGS0008 penetrated the cerebrospinal fluid and was eliminated slower than from plasma. The in vitro metabolism study indicated that MGS0274 was rapidly hydrolyzed to MGS0008, which was not further metabolized. After the intravenous administration of MGS0008 to rats and monkeys, almost all the dose was excreted unchanged in urine. These results suggested that MGS0274 was, as expected, presystemically hydrolyzed to MGS0008 after gastrointestinal absorption and that MGS0008 was distributed throughout the body without further metabolism and ultimately excreted in urine in the animals. Furthermore, the hydrolytic activity against MGS0274 in the human liver S9 fraction was comparable to that in monkeys, suggesting the possibility of the rapid presystemic hydrolysis of MGS0274 to MGS0008 in humans, as it is in monkeys. Consequently, MGS0274 besylate is expected to function as a preferable prodrug in humans.